Mechanisms of Aerobic Exercise Upregulating the Expression of Hippocampal Synaptic Plasticity-Associated Proteins in Diabetic Rats - Jingjing Li; Yuran Liu; Beibei Liu; Feng Li; Jingyun Hu; Qian Wang; Mingming Li; Shujie Lou (Neural Plasticity)
We investigated the effects of aerobic exercise on the expression of hippocampal synaptic plasticity-associated proteins in rats with type 2 diabetes and their possible mechanisms. A type 2 diabetes rat model was established with 8 weeks of high-fat diet combined with a single intraperitoneal injection of streptozotocin (STZ). Then, a 4-week aerobic exercise intervention was conducted. Memory performance was measured with Y maze tests. The expression and activity of synaptic plasticity-associated proteins and of proteins involved in the PI3K/Akt/mTOR, AMPK/Sirt1, and NFκB/NLRP3/IL-1β signaling pathways were evaluated by western blot. Our results show that aerobic exercise promotes the expression of synaptic plasticity-associated proteins in the hippocampus of diabetic rats. Aerobic exercise also activates the PI3K/Akt/mTOR and AMPK/Sirt1 signaling pathways and inhibits the NFκB/NLRP3/IL-1β signaling pathway in the hippocampus of diabetic rats. Therefore, modulating the PI3K/Akt/mTOR, AMPK/Sirt1, and NFκB/NLRP3/IL-1β signaling pathways is probably the mechanism of aerobic exercise upregulating the expression of hippocampal synaptic plasticity-associated proteins in diabetic rats.